IMPLEMENTASI PBL BERBASIS KOTAK BUDAYA UNTUK MENINGKATKAN HOTS SISWA KELAS V SDN 01 PUNTEN - Dinda Oktafia Wardani; Arina Restian; Nur Suhartanti (CV. ADIBA AISHA AMIRA, 2026)
Education in the global world emphasizes the need for students to have High Order Thinking Skills (HOTS). By using problem-based learning (PBL) and media-based Culture Box, this study aims to improve the HOTS ability of fifth grade students of SDN Punten 01 Batu. Classroom Action Research conducted in two stages or cycles is the method used in this study. In the pre-cycle, students' HOTS ability averaged 62.90%, which was categorized as lacking. After the implementation of PBL in cycle I without the Cultural Box media, students' HOTS ability increased to 71.85%, but did not reach the target. In cycle II, with the implementation of PBL based on Kotak Budaya media and technology integration, students' HOTS ability increased significantly to 90.38%, which was categorized as excellent. This study shows that the use of Kotak Budaya media and PBL method is effective in improving students' HOTS ability, supports educational theories about the importance of media and technology in learning, and makes a practical contribution by proposing an innovative and effective learning model for basic education.